Pengaruh Pemberian Ekstrak Daun Pepaya (Carica papaya L) terhadap Folikulogenesis Mencit (Mus musculus) - Enni Mutiati; Akhmad Ferdiansyah; Afifatur Rohmah (Jurnal Biosilampari : Jurnal Biologi, 2024)
Contraception is an effort to prevent or delay pregnancy. One natural contraceptive that can be used is papaya leaves (Carica papaya L). Papaya leaves (Carica papaya L) contain alkaloids, flavonoids, tannins and saponins which are thought to have antifertility effects. Alkaloids can suppress FSH and LH hormones while flavonoids have receptors similar to the estrogen hormone, but it doesn't function like estrogen, so that there is an emphasis on LH hormone and there is an inhibition of Folliculogenesis. The aim of this research is to determine the effect of giving papaya (Carica papaya L) leaf extract on the folliculogenesis of mice (Mus musculus). This research used a Completely Randomized Design (CRD) with 4 treatments and 4 replications. The samples used are mice (Mus musculus) strain Balb-C, then the data obtained will be analyzed descriptively and using Chi-Square. The results obtained from this research are that papaya leaf extract has an effect on the estrus cycle, which is lengthened in the diestrus phase, and can reduce the number of primary follicles, secondary follicles, and de Graff.